Scrutinizing Dayah’s Strategies In Shaping Student Characters: A Qualitative Study - Teuku Zulkhairi; Ibnu Hajar (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Many attempts have been made to shape the character of students, but not all of them have yielded satisfactory results. This article aims to investigate how dayah, an Islamic boarding school in Aceh, Indonesia, shapes the character of students. It involved three leading dayah in Aceh namely Dayah Darul Munawwarah in Pidie Jaya District, Dayah Babussalam Al-Hanafiyyah in North Aceh District, and Dayah Darul Ihsan in Aceh Besar District. The data for this qualitative study was collected through participant observation and in-depth interviews with twelve key informants. Then, qualitative descriptive techniques were used to analyze the data. The results showed that students at these educational institutions have characters that are beneficial to citizens such as mutual respect, frugality, discipline, critical thinking, and being protected from bad habits. These characters were formed by a number of treatments and conditions experienced by students while studying in dayah. Apart from interacting with dayah students, teachers, and employees, dayah students also interact with the community which allows them to gain access to the real world and directly confront community problems. This finding leads to some suggestions for teachers, educational institutions, and policymakers to adopt the education system practiced by dayah in shaping student characters.